Combining the G-particle-hole hypervirial equation and the hermitian operator method to study electronic excitations and de-excitations - Valdemoro, Carmela (2012)
The first aim of this paper is to give an overview of the contracted equations theory (Valdemoro in Adv Chem Phys 134. Wiley, New York, 2007) leading to the description of the G-particle-hole Hypervirial equation (GHV) (Alcoba et al. in Int J Quantum Chem 109:3178, 2009; 111:937, 2011; J. Phys. Chem. A 115:2599, 2011; Valdemoro et al. in Int J Quantum Chem 109:2622, 2009; 111:245, 2011). Our second aim here is to show the suitability to combine the GHV method with the Hermitian Operator (HO) method of Bouten et al. (Nucl Phys A 202:127, 1973; 221:173, 1974) for obtaining various energy differences of a system spectrum when the G-particle-hole matrix and the energy of an almost mono-configurational state is known. Two simple applicative examples of the combined GHV-HO performance are reported. These examples constitute a preliminary test showing that, provided that a G-particle-hole matrix corresponding to a conveniently chosen mainly mono-configurational state is known, this combined method can yield an accurate energy value for a highly correlated state which would be hard to obtain directly with the GHV. © 2011 Springer Science+Business Media, LLC.